Insights into Multicultural Competence of Early Childhood Teacher Candidates in Indonesian Islamic Higher Education - Pratiwi, Hardiyanti; Dwiningrum, Siti Irene Astuti; Riwanda, Agus; Minasyan, Sona (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
This study investigates multicultural attitudes among 168 ECE teacher candidates from four state Islamic universities in Indonesia, using a quantitative descriptive design and the Multicultural Attitudes Survey for Teachers. Results indicate a high average multicultural attitude score of 74.12, with candidates demonstrating confidence in managing multicultural classrooms and promoting cultural pride among children. However, their attitudes are primarily based on personal interactions rather than formal coursework. Interviews with 27 respondents further explore multicultural education practices during teaching practicum, revealing a need for improved collaboration with parents and greater emphasis on multicultural education in both teacher education and ECE curricula. Practical implications include integrating multicultural education into teacher education programs, fostering experiential learning for attitude development, and expanding multicultural education coverage in ECE curricula to enhance children's multicultural awareness.